Evaluation of seasonal variation and the optimization of reducing sugar extraction from Ulva prolifera biomass using thermochemical method - Dave N.; Varadavenkatesan T.; Singh R.S.; Giri B.S.; Selvaraj R.; Vinayagam R. (My University, 2025)
Green macroalgae comprise significant amount of structural carbohydrates for their conversion to liquid biofuels. However, it generally relies on species characteristics and the variability in seasonal profile to determine its route for bioprocessing. Hence, this study was conducted to analyze the indigenous marine macroalgal strain (Ulva prolifera) with respect to periodic trend and reducing sugar extraction. Consequently, in our investigation, the monthly variation in sugar profile and bioethanol yield was assessed between the monsoon and post-monsoon seasons, of which relatively high reducing sugar and fermentative bioethanol yield of about 0.152 ± 0.009 g/gdw and 6.275 ± 0.161 g/L was obtained for the October-month isolate (MITM10). Thereafter, the biochemical profile of this collected biomass (MITM10) revealed carbohydrate 34.98 ± 3.30%, protein 12.45 ± 0.49%, and lipid 1.93 ± 0.07%, respectively, on dry weight basis. Of these, the total carbohydrate fraction yielded the maximum reducing sugar of 0.156 ± 0.005 g/gdw under optimal conditions (11.07% (w/v) dosage, 0.9 M H2SO4, 121°C for 50 min) for thermal-acid hydrolysis. Furthermore, the elimination of polysaccharides was confirmed using the characterization techniques scanning electron microscopy (SEM) and Fourier transform infrared (FT-IR) spectroscopy. Therefore, the present thermochemical treatment method provides a species-specific novel strategy to breakdown the macroalgal cell wall polysaccharides that enhances sugar extraction for its utilization as an efficient bioenergy resource. © 2021, The Author(s).